2021
DOI: 10.1139/cjm-2021-0158
|View full text |Cite
|
Sign up to set email alerts
|

Comparative prevalence and diversity of Campylobacter jejuni strains in water and human beings over a 1-year period in southwestern Alberta, Canada

Abstract: Campylobacter jejuni was isolated from diarrheic people, river water (Oldman River watershed), wastewater, and drinking water over a 1-year period in southwestern Alberta (2008-2009). High rates of campylobacteriosis were observed during the study period (≥115 cases/100K). Infections occurred throughout the year, with a peak in late summer and early autumn. The majority of infections occurred in people living in Lethbridge. Campylobacter jejuni was not isolated from municipal drinking water. In contrast, the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…Moreover, C. jejuni isolated from surface waters corresponded to genotypes different from those of wild birds or recurring clinical isolates. Surface water contamination appears not to be associated with human recurring or wild bird isolates [47]. However, the frequent presence of C. coli could disrupt the isolation of C. jejuni strains because we selected a limited number of colonies.…”
Section: Ordermentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, C. jejuni isolated from surface waters corresponded to genotypes different from those of wild birds or recurring clinical isolates. Surface water contamination appears not to be associated with human recurring or wild bird isolates [47]. However, the frequent presence of C. coli could disrupt the isolation of C. jejuni strains because we selected a limited number of colonies.…”
Section: Ordermentioning
confidence: 99%
“…By contact with these surface waters, animals such as bovines, chickens and wild birds could also become contaminated. Via their faeces, these animals contaminated fields, which become a vector of contamination for other animal food production and waters [47,50]. Moreover, indirect exposure to surfaces contaminated with bird faeces has been linked to disease in young children [51].…”
Section: Ordermentioning
confidence: 99%
“…This is a concern that is not entirely restricted to the developing world, however, with many developed countries having high prevalence of the pathogen group. For example, it was found that 9.1% of diarrheic patients in Alberta over a one-year period were positive for Campylobacter (Inglis et al, 2021). Additionally, some wildlife species consumed by humans contained antimicrobial resistant (AMR) strains of Campylobacter spp., which may have important implications to AMR transmission dynamics and public health (Sasaki et al, 2013).…”
Section: Public Health Implicationsmentioning
confidence: 99%